Ethical Abnegation: Insights from Lonergan - Pauley, Amy (Université Saint-Paul / Saint Paul University, 2017)
The overarching intent of the present work is to identify features of the problem of ethical abnegation and to offer solutions to the problem for the sake of promoting ethical reflection. This project follows a method of problem and response. This involves identifying and responding to elements within ethical theory that contribute to the problem of ethical abnegation. We will offer accounts of the work of Alasdair MacIntyre (chapter 2), Charles Taylor (chapter 3) and Bernard Lonergan (chapter 4 to chapter 8). Each author, in his own manner, identifies features of ethical theory that can foster and even promote ethical abnegation. Based on the research findings, we propose that Lonergan's method for intentionality analysis advances the works of MacIntyre and Taylor on the topic of ethical abnegation. Lonergan's method treats the operations of responsible consciousness, different stages of meaning and patterns of experience and provides a theoretical framework for identifying features of the problem of ethical abnegation and its possible solutions in both ethical theory and interiority and thereby, provides a framework for self-appropriating tools that aid subjects in pursuing ethical reflection on social goods and values. In chapters four and five, we refer to the possibility of developing responsible interiority and moral conversion. These chapters also refer to Lonergan’s framework for differentiating among stages of meaning and multiple concerns that can facilitate moving back and forth between stages and concerns to promote ethical reflection. Chapter six offers Lonergan’s account of the theological tools available to advance the project of contending with ethical abnegation. In particular, theological categories can refer the subject to the need of God’s grace and religious conversion to overcome despair and initiate a loving orientation to do good for others. Chapters seven and eight provide explanations for how Lonergan’s account of the patterns of experience and in particular, the dramatic pattern of experience can facilitate loving orientation to God as a constituent dimension of ordinary experience. The explicability of Lonergan’s tools for identifying and mitigating the challenges of ethical abnegation will be shown to provide justification for the present work’s proposal that Lonergan’s method advances MacIntyre and Taylor’s project of enhancing ethical theory to promote ethical reflection.
Keywords: Bernard Lonergan; Ethics; Interiority; Patterns of Experience; Dramatic Pattern of Experience; Aesthetic and Artistic Patterns of Experience; Charles Taylor; Alasdair MacIntyre